Mega construction projects in South Africa: critical complexity - Mashegoana, Gcobisa (My University, 2019)
Mega construction projects (MCPs) represent one of the strategic options towards achieving sustainable development objectives in countries at different levels of development; the MCP’s success is reported to be significantly lower in developing countries than in those with more mature economies. South Africa is not immune from this as recent projects have shown. Statistics of challenged and failed mega projects testify that the impact of cultural complexities on mega project implementation over the years has become a talking point that needs a deeper understanding. This is pertinent with mega projects as strategic alliances exacerbate culture and national cultural differences which would require more harmonising to effect utmost success. The possibility of cultural disruptions in implementing Mega Construction Projects (MCPs) in South Africa using Medupi and Kusile coal plant projects as cases for this study was explored with the intention of enlightening project stakeholders in order to assist developing countries achieve their sustainable development objectives and overcome the challenges that hinder the successful development of MCPs. Questionnaires and interviews were held with implementing agencies and key personnel and permission was sought to peruse through relevant documents. Analysis of the qualitative data was performed using content analysis and thematic analysis of transcribed interviews. Based on the findings, the study results reveal that there are cultural disruptions that can be found in implementing mega construction projects, ignoring and mismanaging these cultural differences could lead to massive project delays
Thesis presented in partial fulfillment of the requirements for the degree of Masters in Construction Project Management to the School of Construction Economics and Management, University of the Witwatersrand. August 2019